Analisis Unsur Hara Pupuk Organik Cair dari Limbah Ikan Mujair (Oreochromis mosambicus) Danau Lindu dengan Variasi Volume Mikroorganisme Lokal (MOL) Bonggol Pisang - Lepongbulan, Winda; Tiwow, Vanny M. A.; Diah, Anang Wahid M. (Universitas Tadulako, 2017)
The Lake Lindu is one of the potential water resources in Central Sulawesi with various species of fish and one of the most commonly found fish are species mujair fish. Mujair fish processing wastes such as offal can be polluted the environment if not managed properly. The study aim is to determine the contents of NPK nutrients in the liquid organic fertilizer by adding MOL banana weevil. The contents of nitrogen (N), phosphorus (P), and potassium (K) was determined by using spectro direct. The NPK contents in the liquid organic fertilizer of mujair fish waste from Lake Lindu reached the maximum NPK contents of nitrogen (N) of 0.311% by addition 100 mL MOL banana weevil, phosphorus (P) 0.167% by addition 150 mL of MOL banana weevil, and potassium (K) of 0.037% by addition 150 mL MOL banana weevil.